2010
DOI: 10.1103/physrevlett.105.226802
|View full text |Cite
|
Sign up to set email alerts
|

Giant Piezoresistance Effects in Silicon Nanowires and Microwires

Abstract: The giant piezoresistance (PZR) previously reported in silicon nanowires is experimentally investigated in a large number of depleted silicon nano- and microstructures. The resistance is shown to vary strongly with time due to electron and hole trapping at the sample surfaces independent of the applied stress. Importantly, this time-varying resistance manifests itself as an apparent giant PZR identical to that reported elsewhere. By modulating the applied stress in time, the true PZR of the structures is found… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
146
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 24 publications
10
146
1
3
Order By: Relevance
“…Therefore, high-sensitivity piezoresistive transduction, enhanced by an asymmetric beam profile at rest, does not require extraordinarily large piezoresistive coefficients as those reported on high-resistivity bottom-up NWs, which reach up to 1,000 and above 21 . Nevertheless, larger gauge factors are still expected for bottom-up NWs as compared with their top-down counterparts according to the literature 23,24 . In fact, a larger gauge factor for bottom-up SiNWs explains why the quadratic component of the resistance variation with vibration is only detected for these devices (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, high-sensitivity piezoresistive transduction, enhanced by an asymmetric beam profile at rest, does not require extraordinarily large piezoresistive coefficients as those reported on high-resistivity bottom-up NWs, which reach up to 1,000 and above 21 . Nevertheless, larger gauge factors are still expected for bottom-up NWs as compared with their top-down counterparts according to the literature 23,24 . In fact, a larger gauge factor for bottom-up SiNWs explains why the quadratic component of the resistance variation with vibration is only detected for these devices (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The so-called giant piezoresistance effect has indeed been explored for electrical read-out of highfrequency SiNW resonators 2 . Several studies in top-down SiNWs have not been able to find giant values of piezoresistance coefficients 23,24 .…”
mentioning
confidence: 99%
“…7 Recently, gauge factors of G 1000 were reported for silicon oxycarbonitride polymer-derived ceramic 5 and a G = 843 for a silicon-metal hybrid. 8 A lot of excitement was produced by the report of giant piezoresistivity in silicon nanowires, 9,10 with the latest room temperature value reported being G = 280. 11 The earliest work hinting at a higher piezoresistive effect in n-type SiGe alloys of high Ge compositions was performed by R. W. Keyes in 1957.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations. Interestingly, the electrical transport properties of strained h111i and h110i oriented one-dimensional Si nanostructures have been studied experimentally, [33][34][35][36][37][38] while very few reported on the understanding of the strained h100i orientated Si through experiments. 39 The current understanding of the electrical transport properties of strained h100i-oriented Si was limited by theoretical considerations.…”
mentioning
confidence: 99%
“…7,11 For Si, efforts have been paid to alter the carrier transport properties induced by strain in order to find highly sensitive strain gauges or a more effective mode to enhance the carrier mobility by theoretical calculations [21][22][23][24][25][26][27][28][29][30][31] or experiments. [32][33][34][35][36][37][38] It has been well demonstrated that the orientation, size, doping type, and level as well as the strain state are the primary factors 22,26,30,31 affecting the band structure, carrier effective mass, and electric properties for strained crystalline Si. In terms of directional considerations, the h100i, h110i, and h111i are the most important directions for the electrical transport properties of strained Si (particular one-dimensional Si) in practical applications or theoretical investigations.…”
mentioning
confidence: 99%